Overview of Financial Services in the 5.0 Era - Masrina, Dinda Awaliah Ramadhani (UMBanjarmasin, 2023)
overview of financial services in the 5.0 era. Era 5.0 is a digital era characterized by the rapid development of information and communication technology. Financial services are one of the sectors significantly affected by this development. This article provides an overview of the changes and transformation of financial services in the 5.0 era. This research uses a descriptive method and collects data from various reliable sources, including literature studies and recent publications. The analysis shows that the 5.0 era has brought significant changes in financial services. Technologies such as artificial intelligence, big data, blockchain and the Internet of Things have changed the way financial services are provided and accessed by users. Some important trends in financial services in the 5.0 era include digitalization, personalization, integration, and security. In addition, the adoption of new technologies such as biometric technology and digital payments is increasing. However, there are also challenges that need to be overcome, such as data security, privacy, and financial inclusion. This research provides valuable insights into the development of financial services in the 5.0 era and its implications for financial industry players.